Evaluating Aerobic Endurance in Soccer Academy Players Through VO2Max Assessment - Utama, Kokoh Prasetya; Mardhika, Riga (Journal of Sport and Exercise Science, 2025)
Purpose: This study aims to analyze the aerobic endurance of Soccer players in the Academy U-15 age group through VO2max measurement. Soccer is a popular sport that requires optimal physical fitness, one of which is indicated by the VO2max value, which describes the body's capacity to utilize oxygen during intensive physical activity. VO2 max is an important indicator for determining a player's aerobic endurance. Materials and Methods: The research method used is a quantitative descriptive approach, utilizing the bleep test (multi-stage fitness test) to measure the VO2 max level of players. This study involved 24 samples selected by purposive sampling based on specific criteria. The data obtained were then analyzed using VO2max norms to classify the aerobic endurance levels of the players. Result: The study's results showed that Soccer Players Academy's aerobic endurance varied, with 8% being "very poor," 50% being "poor," 17% being "fair," 21% being "good," and 4% being "excellent." Most players fell into the "poor" category, indicating a need to improve their aerobic fitness. Conclusion: Based on these findings, it is recommended that additional training programs, such as interval training and cross-country, be implemented to improve players' VO2 max. In addition, coaches are expected to pay special attention to training planning that focuses on physical endurance and ensures a balance of nutrition and healthy lifestyles for players. This study contributes to developing measurable physical fitness-based soccer coaching programs.